If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -42 = 3(x + -2) + -9 Combine like terms: 12 + -42 = -30 -30 = 3(x + -2) + -9 Reorder the terms: -30 = 3(-2 + x) + -9 -30 = (-2 * 3 + x * 3) + -9 -30 = (-6 + 3x) + -9 Reorder the terms: -30 = -6 + -9 + 3x Combine like terms: -6 + -9 = -15 -30 = -15 + 3x Solving -30 = -15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -30 + -3x = -15 + 3x + -3x Combine like terms: 3x + -3x = 0 -30 + -3x = -15 + 0 -30 + -3x = -15 Add '30' to each side of the equation. -30 + 30 + -3x = -15 + 30 Combine like terms: -30 + 30 = 0 0 + -3x = -15 + 30 -3x = -15 + 30 Combine like terms: -15 + 30 = 15 -3x = 15 Divide each side by '-3'. x = -5 Simplifying x = -5
| 100=33+x | | 15=(5k-13) | | 2x^2=1080 | | 32y^2+5y+6y= | | 40=-8(x+7) | | 700=84+28d | | -3(r+8)=48 | | 2x=250+x | | -15x+32=x | | 15w-19w=24 | | .5y-1=.33 | | -(3x+4)+15=6-4x | | (6-4)(6+3)=18 | | 37-13=4(x-6) | | 38=-1X | | y=3x+(2x-1) | | 40x+x^2=624 | | 7(2*-3)+3=24 | | 90+51=2x+1 | | 5/6h-7/13=-3/4h-13/6 | | 2x+6=-6x+54 | | 2y+3(x+2)=-5 | | x/2(28-x)=96 | | -38-(-49)=x/12 | | 6x+2+107=163 | | 2y=y+2 | | -3x-2=30 | | 26=4x-11 | | .78log=x | | x^2-x-30=8 | | 9x+2y=66 | | -3k+6k=-6 |